Time and wavelength diversity schemes for transdermal optical wireless links - Almajdoubah, Rawan; Hasan, Omar (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Transdermal optical wireless communication systems have gained significant research and commercial attention in recent years. While using the skin as a transmission medium, the performance of such a system is influenced by the transdermal channel conditions between the transmitter and receiver. Indeed, for transdermal optical channel links, the performance of a linked communication system can be significantly affected by skin- induced attenuation and pointing errors. Extra attention has been given to diversity techniques to anticipate this. This research examines a conventional transdermal optical wireless system by analyzing the outage probability, an important performance parameter that has not been previously evaluated for such systems using the same method. In an examination of outage probability, both skin-induced attenuation and stochastic spatial jitter, also referred to as pointing error effects, are included. The usefulness of this topic is demonstrated using analytical formulas and results that determine the probability of system outage under various skin channel conditions and varying levels of stochastic pointing faults. Simulation model using Monte- Carlo simulation method was conducted using MATLAB to validate our suggestions. The simulation results showed a good agreement with numerical results, which proved the effectiveness of using wavelength and time diversity schemes to enhance transdermal optical wireless based systems.